(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The need for demolition, repairs and renewal of concrete and masonry structures is rising all over the world, more so in the developing countries. It is highly desirable that the waste materials of concrete and bricks generated after the demolition of old structures are reutilized in an effective manner to reduce the environmental damages caused by excessive reckless quarrying for earth materials and stones. Also, this will reduce pressure on finding new dumping ground for these wastes, thus further saving the natural environment and ecosystem.The present investigation is focused on use of demolished concrete in order to reduce construction cost and resolve housing problems faced by the low-income communities of the world. The crushed demolished concrete is segregated by sieving to obtain required sizes of aggregate. Several tests were conducted to determine the aggregate properties before recycling it into new concrete. This investigation shows that the demolished concrete that are obtained from site make good quality concrete.